UMPSA performs korban ritual in conjunction with Aidiladha 1446H - Siti Nur Azwin, Zulkapri (UMPSA, 2025)
GAMBANG, 10 June 2025 – In conjunction with the Hari Raya Aidiladha celebration, Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), through the Centre for Islamic and Human Development (PIMPIN), in collaboration with the Institute of Postgraduate Studies (IPS) and the UMPSA Postgraduate Association 2025 (PGA 2025), organised the Ibadah Korban programme involving the slaughtering of nine cows at UMPSA Gambang Campus.